On the margins of the hydrosocial: quasi-events along a stagnant river - Ley, Lukas (Geoforum, 2018)
This article investigates stagnation as a product of hydrosocial relations in light of ethnographic research conducted in the port city of Semarang, Indonesia. In Semarang’s coastal north, river water spills daily into neighbourhoods during high tide, and often stagnates in houses and streets. While recent studies have shown that water governance is a form of social control, reproducing (infra)structures of subjugation and social inequality, little attention has been paid to the margins of water infrastructure, especially in cities. By focusing on stagnation, this article examines hydrosocial arrangements in the margins of postcolonial drainage infrastructure. When the peripheral and densely populated neighbourhoods in Semarang’s north are flooded during high tide, residents resort to private or semi-public pumps to get rid of stagnant water. Residents deplore insufficient state attention to their area, reflected in collapsing or seeping riverbanks. A relatively reliable flood prevention is the timely and regular raising of house floors and streets. The municipality responds to dramatic rates of land subsidence (10-15cm/year) by raising roads and riverbanks. Yet, many dwellings along the Banger River have been destroyed by intruding sea water and left behind in ruins, suggesting a permanent failure of the city’s drainage system. Residents bear the brunt of supplementary infrastructural labour, their efforts of infrastructural repair and maintenance sustaining a bare minimum of safety. The article mobilizes Elizabeth Povinelli’s concept of quasi-events to understand the hydrosocial relations that shape peoples’ precarious relation with drainage infrastructure as unequal yet generalized. Quasi-events, that is, efforts to hold water at bay, suck energy and resources from marginalized residents. As such, the article argues that the margin of the hydrosocial is integral to the political configuration of land and water.